Manufacturing high technology handbook - Tijunelis, Donatas; McKee, Keith E. (Marcel Dekeer, 1987)
Providing single-volume coverage of the full range of manufacturing techniques that can accommodate multiple products for more than one life cycle, control product quality parameters, and minimize in-process inventory, Manufacturing High Technology Handbook is extensively referenced with bibliographic citations of the literature and illustrated with over 400 diagrams, photographs, and tables that clearly demonstrate concepts, procedures, and equipment